Effect of catalyst on the producer gas composition from co-gasification of glycerol/fat mixtures - Cruz, Amaro (2022)
In this work, steam reforming of crude glycerol and animal fat mixtures was studied. The tests were carried out at temperatures of 700 °C and 750 °C in a fixed bed reactor using activated alumina or dolomite particles, to evaluate the catalytic capacity of these minerals in the removal of tar from the producer gas. The gas produced was quantified and analyzed by gas chromatography, and it was concluded that its composition is greatly influenced by the bed material used. The results obtained showed that dolomite is more effective in reducing the tar content, evidencing its ability to catalyze the tar reform reactions and promoting the water-gas shift reaction. Consequently, using dolomite as a catalyst, a producer gas with 47–48 vol% in H and 27–30 vol% in CO2 was obtained, while using a bed of alumina particles, a gas with a high CO content (45–48 vol%) and lower H content (34–37 vol%) was produced.